Metabolic characteristics of human subcutaneous abdominal adipose tissue after overnight fast. - Frayn, K; Humphreys, S (2012)
Subcutaneous abdominal adipose tissue is one of the largest fat depots and contributes the major proportion of circulating nonesterified fatty acids (NEFA). Little is known about aspects of human adipose tissue metabolism in vivo other than lipolysis. Here we collated data from 331 experiments in 255 healthy volunteers over a 23-year period, in which subcutaneous abdominal adipose tissue metabolism was studied by measurements of arterio-venous differences after an overnight fast. NEFA and glycerol were released in a ratio of 2.7:1, different (P < 0.001) from the value of 3.0 that would indicate no fatty acid re-esterification. Fatty acid re-esterification was 10.2 ± 1.4%. Extraction of triacylglycerol (TG) (fractional extraction 5.7 ± 0.4%) indicated intravascular lipolysis by lipoprotein lipase, and this contributed 21 ± 3% of the glycerol released. Glucose uptake (fractional extraction 2.6 ± 0.3%) was partitioned around 20-25% for provision of glycerol 3-phosphate and 30% into lactate production. There was release of lactate and pyruvate, with extraction of the ketone bodies 3-hydroxybutyrate and acetoacetate, although these were small numerically compared with TG and glucose uptake. NEFA release (expressed per 100 g tissue) correlated inversely with measures of fat mass (e.g., with BMI, r(s) = -0.24, P < 0.001). We examined within-person variability. Systemic NEFA concentrations, NEFA release, fatty acid re-esterification, and adipose tissue blood flow were all more consistent within than between individuals. This picture of human adipose tissue metabolism in the fasted state should contribute to a greater understanding of adipose tissue physiology and pathophysiology.